Reading the Character of the Pata Dela Customary Law in Sustainable Forest Management and Food Security of the Ngadhu Bhaga Community - Maria Theresia Geme; Ferdinandus Ngau Lobo; Benediktus Peter Lay; Mary Grace Megumi Maran (JUSTISI, 2026)
This study aims to discover legal characteristics, namely behavioral norms in pata dela, particularly those related to sustainable forest development and food security. The method used in this study is empirical legal research conducted in Rakalaba Village, West Golewa District, Ngada Regency, East Nusa Tenggara Province. The approaches used in this study are legal sociology, philosophy, legal history, and conceptual approaches. The data used in this study are primary and secondary data.  The data were processed and then analyzed using descriptive qualitative methods. The novelty of this study focuses on the character of legal norms, namely the commands and prohibitions contained in the local wisdom of pata dela. These legal norms serve as guidelines for realizing sustainable forestry development that has an impact on food security. The results of the study show that the Ngadhu bhaga customary law community has an oral tradition called pata dela or ancestral teachings. Pata dela contains primary legal norms, namely commands marked with the word bodha, which means mandatory. In addition, pata dela also contains prohibitions marked with the word ma'e, which means forbidden. Pata dela plays a role in sustainable forest development based on customary law. For example, in the command “Bodha sepe ne'e de kenge, latu ne'e de kabu” and the prohibition “Ma'e rawu dhapi kabu, ma'e sa'a dhapi tara”. Through this oral tradition, the community can ensure that plants continue to grow. Pata dela also has implications for realizing food security for the Ngadhu Bhaga community. It contains commands and prohibitions that reflect an ecological understanding that food crops must be sustained so that they remain available over time. Food security is not only a matter of the availability of food at present, but also a guarantee that future generations will continue to have access to quality food sources. Conclusion of this study is that Pata dela contains primary legal norms that include commands and prohibitions. Pata dela is still alive and is still used as a guideline in sustainable forest development to achieve food security.